PENGARUH PIJAT PERINEUM PADA KEHAMILAN TRIMESTER III TERHADAP ROBEKAN PERINEUM PRIMIGRAVIDA DI PUSKESMAS JAGIR SURABAYA: The Effect Of Perineal Massage During The Third Trimester Pregnancy On The Prevention Of Primigravida Perineal Rupture at Community Health Center In Jagir Surabaya - Fritria Dwi Anggraini; Yasi Anggasari (LPPM - STIKES Pemkab Jombang, 2019)
Abstract : Perineal rupture may occur spontaneously (ruptured) or deliberately (episiotomy). An attempt to Flex the perineum perineum massage among others who haven't performed in clinics jagir. The objective of this research was to find out the effect of perineal massage during the third trimester of pregnancy on the prevention of primigravida perineal rupture in Community Health Center in Jagir -Surabaya. The research design was Quasi-experimental with post-test only group model. The population was all pregnant mothers - of primigravida physiologic category of the third trimester - who delivered at Community Health Center in Jagir Surabaya with its sample of 20 respondents, that is, 10 respondents of the treatment group and 10 respondents of the control group. The independent variable was perineal massage, and the dependent variable was perineal rupture. The data collection was carried out using SOP and partographic sheet / medical record. The data were analyzed by Mann Whintney test with ? = 0.05. The Result of the research showed that almost all respondents (80.0%) did not experience perineal rupture in treatmen group and most (60.0%) of those respondents experiencing torn perineum were suffering from perineal tear in control group. The result of the statistic test using Mann Whitney showed p = 0.001 <? = 0.05, then Ho was refused, meaning there was effect of perineal massage during the third trimester pregnancy on the prevention of primigravida perineal rupture at Community Health Center in ??Jagir surabaya. Respondents who do the massage the perineum almost everything does happen rips therefore massage the perineum can Flex the perineum so as not happening rips the perineum. Therefore it was suggested that the health workers encourage the pregnant mothers to have perineal massage treatment during theperiod of maternity preparation.